The genome of the zebra mussel, Dreissena polymorpha: a resource for comparative genomics, invasion genetics, and biocontrol. Issue 2 (13th December 2021) - McCartney, Michael A; Auch, Benjamin; Kono, Thomas; Mallez, Sophie; Zhang, Ying; Obille, Angelico; Becker, Aaron; Abrahante, Juan E; Garbe, John; Badalamenti, Jonathan P; Herman, Adam; Mangelson, Hayley; et al.
Abstract : Zebra mussels are one of the world's most damaging invasive species. Native to Eurasia, they have continued to spread rapidly though Europe and in recent decades through North America, causing billions of dollars in economic damage and dramatically altering the ecosystems of infested lakes and rivers. Here we report the sequencing of the zebra mussel genome which will be an important tool for invasive species research and biocontrol efforts. Abstract: The zebra mussel, Dreissena polymorpha, continues to spread from its native range in Eurasia to Europe and North America, causing billions of dollars in damage and dramatically altering invaded aquatic ecosystems. Despite these impacts, there are few genomic resources for Dreissena or related bivalves. Although the D. polymorpha genome is highly repetitive, we have used a combination of long-read sequencing and Hi-C-based scaffolding to generate a high-quality chromosome-scale genome assembly. Through comparative analysis and transcriptomics experiments, we have gained insights into processes that likely control the invasive success of zebra mussels, including shell formation, synthesis of byssal threads, and thermal tolerance. We identified multiple intact steamer-like elements, a retrotransposon that has been linked to transmissible cancer in marine clams. We also found that D. polymorpha have an unusual 67 kb mitochondrial genome containing numerous tandem repeats, making it the largest observed in Eumetazoa. Together these findings create a rich resource for invasive species research and control efforts.